USE OF IMAGE PUZZLE MEDIA IN LEARNING PAI - Sri Dewi Lestari; Sugiarti; Zulfan (Journal of Quality Islamic Education Research, 2025)
The purpose of this article is to analyze the use of jigsaw puzzle media in Islamic Religious Education learning. This study uses the library research method. In the learning process, the use of media is inseparable from the use of media to increase the effectiveness of learning, both general learning and Islamic Religious Education learning. One of the media that can be used by teachers is jigsaw puzzle media because this media can increase students' interest and motivation to learn. Jigsaw puzzle learning media is a simple media that is played by disassembling and reassembling. This media is a learning media that uses puzzle game techniques to sharpen the brain. Jigsaw puzzles consist of a board and several pieces, which when arranged will cover the part of the board that is slightly indented and will become a certain shape. The purpose of using this learning media itself is to make it easier for students to master the learning competencies that have been set, so that the use of jigsaw puzzle media in the Islamic Religious Education learning process can be more effective and enjoyable